Trauma kinematics: assessment of the victim in labor in pre-hospital care (Research, Society and Development, 2021)
Pre-hospital care emerged with the aim of reducing the number of deaths, the length of stay in hospitals and the sequelae resulting from therapeutic delay, in trauma and acute illnesses, as well as in situations involving high-risk pregnant women and newborns. This study aimed to analyze the obstetric occurrences attended by the SAMU in pre-hospital care, aiming to contribute to the improvement of care at the level of primary health care for pregnant women, as well as to plan actions to raise awareness of the population regarding the purpose of the service. mobile pre-hospital care. The data survey was carried out between January and July 2021, by searching for articles indexed in the Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO), with the help of the following databases: PubMed (National Center for Biotechnology Information), Lilacs (Latin American and Caribbean Health Sciences), Nursing Database (BDENF). The need for urgent care at any time during the gestational period requires speed, in addition to quick clinical and critical thinking that corresponds to the patient's real need. This is because the emergency care, the adequate evaluation of the condition and the support alternatives available in the emergency service are essential for the proper outcome of the complication. It is necessary to implement mechanisms to impose specific strategies, since better management in pre-hospital care for the mother/child binomial can prevent severe injuries that culminate in maternal death and equally reduce the chance of complications and neonatal deaths.